Oncogenic role of PDK4 in human colon cancer cells - Leclerc, D; Pham, D N T; Lévesque, N; Truongcao, M; Foulkes, W D; Sapienza, C; Rozen, R (British journal of cancer, 2017)
Background: Cancer cells maintain high rates of glycolysis. Pyruvate dehydrogenase kinases (PDK) contribute to this phenomenon, which favours apoptosis resistance and cellular transformation. We previously reported upregulation of PDK4 in normal mucosa of colorectal cancer (CRC) patients compared with controls and in preneoplastic intestine of our mouse model. Decreased methylation of four consecutive PDK4 CpGs was observed in normal mucosa of patients. Although other members of the PDK family have been investigated for transformation potential, PDK4 has not been extensively studied. Methods: PDK4 methylation in blood of CRC patients and controls was evaluated by pyrosequencing. PDK4 expression in human colon carcinoma cells was down-regulated by RNAi. Cellular migration and invasion, apoptosis and qRT-PCR of key genes were assessed. Results: Pyrosequencing revealed decreased methylation of the same four consecutive CpGs in the blood of patients compared with controls. Cellular migration and invasion were reduced and apoptosis was increased following transient or stable inhibition of PDK4 . Expression of vimentin, HIF-1 and VEGFA was reduced. Conclusions: These studies demonstrate the involvement of PDK4 in transformation. Methylation assessment of PDK4 in the blood may be useful for non-invasive CRC detection. PDK4 should be considered as a target for development of anticancer strategies and therapies